Nutritional Status and Psychological Impairment in Rural Adolescent Girls: Pilot Data From “KOKAN” Region of Western India - Patil, Suvarna; Joglekar, Charudatta; Desai, Maruti; Yadav, Arvind; Sonawane, Swati; Chavan, Rupali; Mohite, Rachana (Frontiers in Public Health, 2018)
Background Adolescence is a period during which psychological foundations are laid down as well as consolidated. Not much information is available on rural Indian adolescent girls and their psychological health. Methods We did a pilot survey of psychological health of 80 adolescent girls residing at KONKAN region of western India.Psychological health was evaluated using Youth Paediatric Symptom Checklist (Y-PSC) consisting of 35 items with maximum score of 70. Those above score of 30 were classified as psychologically impaired. In addition we also collected random blood sample and measured the micronutrients. Macronutrient intake was estimated by 24 hour recall. Results The girls were 14y old ( sd 1.5). In all 35/76 (46.1%) could be classified as psychosocially impaired. There was a high prevalence of micronutrient deficiencies with varying degrees. More than 65% were deficient in calcium, zinc and folic acid. About 22% were anaemic and 36% were vitamin B1 deficient. More than 75% had a low RDA of macronutrients. Those with poor serum calcium concentration had higher psychological score (p<0.05). Fat and calcium intakes were inversely associated with psychological score ( p <0.05 and p <0.001 respectively). Odds ratios for psychological impairment were significant for those with low calcium levels (1.47 (95% CI 1.21, 4.31)), and for those with low calcium intake 1.43 (1.08, 4.21) and low iron intake 3.04 (1.02, 9.26). Conclusion Our pilot data has shown the urgent need to improve the nutrition of adolescent girls, which could improve their psychological health.